Public Perception of Women Who Play Football - Daiva Octaviana; Deswita Supriyatni (Journal of Physical and Outdoor Education, 2026)
This study aims to examine public perceptions of women participating in football, a sport that is still often viewed as deviating from traditional gender norms. The main focus of this research is to understand societal views regarding the presence of female athletes in the field of football and to identify the factors that influence these perceptions, both internal aspects such as knowledge, attitudes, and prejudice, as well as external aspects such as cultural and media influences. This research employed a descriptive qualitative method with a case study approach, conducted in Cipada Village, Cikalongwetan District. Data were collected through in-depth interviews and direct observations involving informants such as football coaches, parents of female players, and members of the general public. The findings reveal that although there is growing support from certain segments of the community, negative perceptions still persist, reflecting the deep-rooted gender stereotypes regarding women's roles in sports. This study is expected to contribute scientifically to the promotion of gender equality and the enhancement of social acceptance of women's participation in football.